Pengaruh Moralitas Individu dan Pengendalian Internal terhadap Kecenderungan Fraud: Systematic Literature Review - Kharisma Febriani; Firly Ni’matussyifa; Dien Noviany Rahmatika (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Accounting Fraud has become a major problem across all industries, causing financial loss and damaging an organization's reputation. In this research, the goal to be achieved is to understand how an individual's morality and internal control influence the occurrence of fraud. Fraud cases in Indonesia have increased along with business growth and developing investment opportunities. Company financial reports are often presented maximally to attract investor interest. This research applies a Systematic Literature Review (SLR) approach. This literature review was carried out by collecting articles published in international and national journals from 2017 - 2024. Of the 336 articles found, 52 articles were taken for further analysis based on certain criteria. Articles collected via Google Scholar, Semantic Scholar, ResearchGate and Garuda. In this study, articles were grouped based on the year in which they were published, the number of authors involved, the research methods used, and the data collection techniques applied. The findings from this study indicate that this subject will be the most discussed in 2022, with 13 related journals. Most of the authors come from the Indonesian Hindu University in the Hita Accounting and Finance journal, contributing 22% of the total articles. The method most commonly used in this research is quantitative, with questionnaires as the main approach to collecting data.